Está en la página 1de 4

1

1
. ) ;
)
;
) ;
) ;
.

) (x) 2 Q(x) 3,
(x)Q(x) 6 .
) (x)Q(x) 8 Q(x) 3, (x)
5.
) (x) = 2x + 4 Q(x) = 3 + x2, (x)Q(x) = 2x + 43 + x2
) (x) = ( 1) x3 + x2 4 3
) (x) = (x + 2) (x 3) x2 + 7 2

2
.)

//

// .
, ,

, .

)
.

.
)
)
) 48
)
)
)
)

)

1
= x(x 4) = (x 6)(x + 2)
) = 12
) + 36
) x(x 6)( x 4)(x + 2) + 36

) x(x 6)( x 4)(x + 2) + 36 = 0

2
= ,
.
: )
)
)

1 x4 1
1 1
) 1 + + 2 + 3 : 4
x x x3
x x
x 2 y2 y4
x 2 xy + y 2
)

(x + y) 2 3xy
xy 2 y3

( )
1 ()
.)


.)

.

.
.)
(x) = 0

.)
(x) = ,
0 . .

.

) ( )

3
)
)
)
)

( )
( = 1 2 )
( )

2 ()
.)


=
.

= =

.
.)


=
=



=
=

)
) ( 60 )
) ( )
)
)
) ( 45 )
) ( )
) (
)

1 ( )
)
= (x 6)(x + 2) = x2 6x + 2x 12 = x2 4x 12 = x(x 4) 12 = 12
)
()

+ 36 = A( 12) + 36 = A2 12A + 36 = (A 6)2


)
x (x 6)( x 4)( x + 2) + 36 = [x(x 4)][(x 6)(x + 2)] + 36 =
()

= AB + 36 =

= (A 6)2 =
= [(x(x 4) 6]2 =
= (x2 4x 6)2
)
x (x 6)(x 4)(x + 2) + 36 = 0

( ())

(x2 4x 6)2 = 0

= 40

x2 4x 6 = 0
4 + 40
4 + 4 10
4 + 2 10
x 1=
=
=
= 2 + 10
2
2
2
x2 = .. 2 10

2 ( )

)

=
= .
)



= = .
= .

)
= , =
= .

3 ( )
)
x3 x 2 x
1 x4 1
1 x4 1
1 1
:
=
=
1
+
+
+
+
+
+
3
:

2
x3 x3 x3 x 4 x3
x3 x 4 x3
x x
x
x3 + x 2 + x + 1 x 4 1
=
: 4
=
x3
x x3
x 2 (x + 1) + (x + 1) (x 2 1)(x 2 + 1)
:
=
=
x3
x 3 (x 1)
=

(x 2 + 1)(x + 1) (x 1)(x + 1)(x 2 + 1)


:
=
x3
x 3 (x 1)

x 3 (x 1)
(x 2 + 1)(x + 1)

=1
x3
(x 1)(x + 1)(x 2 + 1)

x 2 y2 y4
x 2 xy + y 2
y 2 (x 2 y 2 )
x 2 xy + y 2

=
(x + y) 2 3xy
xy 2 y3
x 2 + 2xy + y 2 3xy y 2 (x y)
=

y 2 (x y)(x + y) x 2 xy + y 2
2
= x+y
x 2 + y 2 xy
y (x y)